Stacking Sequence Effect on the Fracture Behavior of Narrow L-Shaped Cross-Ply Laminates: Experimental Study - Pan, Z.Y.; Duan, Q.F.; Zhong, Y.C.; L, i S.X.; Cao, D.F. (Проблемы прочности, 2018)
The stacking sequence effect of narrow L-shaped laminates on the fracture mode was studied. Изучено влияние последовательности упаковки узкого уголка из ламинатов на характер его разрушения.